Edge effects of oil palm ecosystem on insect compositions at boundries of different land use - Abdullah N.-A.; Haris-Hussain M.; Ayob Z.A.; Nasir D.M.; Faszly Rahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus/MyCite